1998
DOI: 10.1677/joe.0.1590389
|View full text |Cite
|
Sign up to set email alerts
|

The hormonal status modulates the effect of neurokinin A on prolactin secretion in female rats

Abstract: We have previously reported that neurokinin A (NKA), a tachykinin closely related to substance P, increases the release of prolactin (PRL) from the anterior pituitary gland of male rats, but not from pituitaries of ovariectomized (OVX) female rats. In this study, we evaluated the influence of estrogens in the action of NKA on PRL secretion in female rats. NKA stimulated the in vitro release of PRL from pituitary glands of OVX-chronically estrogenized rats, and of proestrus and estrus rats, but had no effect in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Candidate genes in this region (from BTA4.0; www.ensembl.org) include pyrophosphatase 2, tachykinin receptor 3, and mannosidase, β A. Both pyrophosphatase 2 and mannosidase are expressed in the mammary gland, and tachykinins have a role in modulating prolactin release during lactation (Pisera et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Candidate genes in this region (from BTA4.0; www.ensembl.org) include pyrophosphatase 2, tachykinin receptor 3, and mannosidase, β A. Both pyrophosphatase 2 and mannosidase are expressed in the mammary gland, and tachykinins have a role in modulating prolactin release during lactation (Pisera et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These ewes were long-term ovariectomized with no estrogen replacement. The induction of NK-1 receptors is estrogen dependent [41], and there is evidence that tachykinins may not affect prolactin release in the ovariectomized rat [42]. Second, SP is rapidly degraded [37], and a 70-nmol dose may not have been sufficient to raise SP levels in the hypophyseal portal system.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, SP-induced BP reduction was also mimicked by microinjection of NK1R and NK2R agonists with equal efficacy, but a long-lasting action was only observed in the presence of NK1R. These data imply that the NG plays an exact opposite role in BP regulation vs NTS and the protective role of estrogen-dependent NKRs expression in the NG and the sensitivity NKRs to SP 47 . Intriguing observations from our recent experiments and other cardiovascular literature have demonstrated that the difference in central and peripheral activation of neuropeptide Y mediates hypotensive 48 and hypertensive action.…”
Section: Ng Plays An Opposite Role In Bp Regulation Compared With That Of Ntsmentioning
confidence: 80%